UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPA MELALUI MODEL COOPERATIVE LEARNING TIPE SNOWBALL THROWING DI KELAS VI SDN 17 SIMAUNG CUMATEH - Sasma, Sasma (Jurnal Manajemen Pendidikan, 2018)
the role of the teacher is very important in PBM and it is expected that the teacher has a good teaching method and is able to choose the right learning method and in accordance with the subject concepts to be delivered. One of the right learning models in science learning is the Snowball Throwing learning model. The problems that want to be studied in this research are: Can the use of the Snowball Throwing learning model improve the results of the split of science in Grade IV students of SDN 17 Simaung Cumateh? The purpose of this action research is to improve the learning outcomes of Grade IV SDN 17 Simaung Cumateh through the Snowball Throwing learning model. This study used two rounds of classroom action research. Each round consists of four stages: planning, implementation, observation, reflection. The target of this research is the fourth grade students of SDN 17 Simaung Cumateh. The data obtained are quantitative and qualitative data. From the results of the analysis of science learning model has a positive impact in improving student learning outcomes which is characterized by an increase in student learning completeness in each cycle, namely cycle I 52.63%, and cycle II 94.37%. The conclusion of this study is Snowball Throwing learning model has a positive influence, which can improve student learning outcomes which is indicated by the average student answers stating that students are interested and interested in the Snowball Throwing learning model so that they become motivated to learn.